Peran Bank Muamalat KCP Sumenep Dalam Usaha Pemberdayaan dan Pengembangan Ekonomi Di Kabupaten Sumenep - S. Hikmah Jamil (Al-Musthofa: Journal of Sharia Economics, 2020)
This study aims to determine the role of Bank Muamalat KCP Sumenep to empowerment and developing the economy in Sumenep Regency. This research uses qualitative methods and descriptive data analysis techniques. The object of research is Bank Muamalat KCP Sumenep. The results showed that the role Bank Muamalat KCP Sumenep is very important to empowerment and developing the economy in Sumenep Regency. These roles are: developing the Hajj and Umrah service business segments, collaborating with educational institutions, as well as marine commodity-based businesses. Adding a repertoire of Islamic economic institutions in Sumenep and creating synergies with the Bank Perkreditan Rakyat Syariah (BPRS) in Sumenep Regency.